Integrated remanufacturing, maintenance and spares policies towards life extension of a multi-component system. (November 2021) - Wakiru, James; Pintelon, Liliane; Muchiri, Peter N.; Chemweno, Peter K.
Highlights: The significance of maintenance to the remanufacturing process is demonstrated. Remanufacturing proposed solution to life extension and spare obsolescence End-user role and influence on remanufacturing decision investigated Remanufacturability indicator defined using empirically relatable and identifiable factors The significance of end-user actions and influence to remanufacturing process is demonstrated. Core condition classified as a function of obsolescence, maintenance actions Abstract: The decision for remanufacturing as a life extension solution for ageing equipment approaching their end of life (EOL), has marginalized the active role of the end-users and maintenance functions, by predominantly considering the remanufacturers (OEM/R) context. However, the decisions influencing the immediate core (used item/part of its component) condition like corrective maintenance actions used, and when to return a core for remanufacturing or exchange with a remanufactured part, are often the end-users responsibility. Factors like remanufacturing cost, alternative maintenance and spare strategies, introduce conflicting preferences, hence an asymmetric relationship between the end-user and the remanufacturer. This paper develops an integrated methodology to optimize maintenance, remanufacturing, and multiple spare strategies (new and remanufactured exchange) jointly, for life extension of an ageing multi-component system with dependencies. The model inculcates the asymmetric relationship to assist the end-user to derive decision support on optimal maintenance and remanufacturing strategies while minimizing the costs. A case study of an ageing turbine rotor assembly of a turbocharger with spare obsolescence demonstrates the utility of the proposed model. The study shows that the approach offers robust decision support, and further demonstrates the significance of the maintenance function and end-user influence in the remanufacturing decision making.